The aesthetic outcome of surgical correction for sagittal synostosis can be reliably scored by a novel method of preoperative and postoperative visual assessment. - Bendon, C; Johnson, H; Judge, A; Wall, SA; Johnson, D (2014)
BACKGROUND: Aims of surgical correction for isolated sagittal synostosis are functional and aesthetic. Multiple surgical techniques exist; however, reliable assessment of aesthetic outcome is poorly documented, limiting direct comparisons. The pinched appearance of the temporal regions is particularly challenging to correct. A visual analogue scale was designed to grade skull shape in patients who had total or subtotal calvarial remodeling for isolated sagittal synostosis. METHODS: Twenty-two assessors graded preoperative and postoperative photographs from 42 consecutive cases of sagittal synostosis under a single surgeon. Five aspects were graded (i.e., narrow elongated skull, frontal bossing, temporal pinching, occipital bullet, and overall shape) from 0 (normal) to 100 (severe). Interobserver and intraobserver agreement were analyzed by calculating within-subject standard deviation, coefficient of variation, and intraclass correlation coefficient. Linear regression analysis determined predictors of outcome. RESULTS: Surgery improved outcome dramatically across all five aspects of skull shape, with a 72.6 to 76.4 percent decrease in severity score. Improvements in severity score were greater after total calvarial remodeling, and type of calvarial remodeling (total versus subtotal) was an independent predictor of outcome in all aspects of skull shape (p≤0.001). Temporal pinching was improved in a subset of patients who also had onlay bone grafts in this region. CONCLUSIONS: Calvarial remodeling is a powerful technique for improving skull shape. A panel can detect gross and subtle aesthetic changes after surgical correction of sagittal synostosis using a visual analogue scale, with moderate interobserver and intraobserver agreement. This provides a tool for future outcome assessment. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.